Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1099/0022-1317-83-10-2443
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence analysis of Tamana bat virus and its relationship with the genus Flavivirus

Abstract: Tamana bat virus (TABV, isolated from the bat Pteronotus parnellii) is currently classified as a tentative species in the genus Flavivirus. We report here the determination and analysis of its complete coding sequence. Low but significant similarity scores between TABV and memberviruses of the genus Flavivirus were identified in the amino acid sequences of the structural, NS3 and NS5 genes. A series of cysteines located in the envelope protein and the most important enzymatic domains of the virus helicase/NTPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…Thirdly, the polymerases of numerous viruses that specifically infect mammalian cells (pestiviruses, hepaciviruses and Tamana bat virus) are phylogenetically related to those of flaviviruses (de Lamballerie et al, 2002) and there is little chance that these viruses originated from the genome of mosquitoes in recent times; for example, it has been suggested that the common ancestor of hepaciviruses GB virus A and C existed 35 mya in primates (Charrel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the polymerases of numerous viruses that specifically infect mammalian cells (pestiviruses, hepaciviruses and Tamana bat virus) are phylogenetically related to those of flaviviruses (de Lamballerie et al, 2002) and there is little chance that these viruses originated from the genome of mosquitoes in recent times; for example, it has been suggested that the common ancestor of hepaciviruses GB virus A and C existed 35 mya in primates (Charrel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2). The region of the flavivirus polyprotein homologous to the CSA ORF includes several cleavage sites for the viral serine proteinase, a series of cysteine residues (in the NS1 gene) and enzymic motifs (in the NS3 gene) responsible for serine protease and helicase/NTPase activities, which are widely conserved among flaviviruses (de Lamballerie et al, 2002). These sites and motifs are present and conserved in the CSA sequence, and the hydropathy profile of the protein deduced by conceptual translation of the ORF sequence is remarkably similar to that of the homologous region of KRV polyprotein (Fig.…”
Section: Extension Of Sequence By Genome Walking and Comparison With mentioning
confidence: 99%
“…This virus was isolated in 1973 from an insectivorous bat in Trinidad (Price, 1978) and for 25 years it remained a taxonomic enigma. It was shown recently to constitute a highly divergent evolutionary lineage within the flaviviruses, constituting a sister group to all other known taxa (de Lamballerie et al, 2002). In contrast to CFAV and KRV, TABV infects only vertebrates and does not replicate in arthropod cells.…”
mentioning
confidence: 99%
“…The corresponding amino acid sequence was then aligned with those of other flaviviruses by using the MUSCLE algorithm (Edgar, 2004). The highly divergent TABV was excluded from this analysis, as a previous study failed to identify its precise phylogenetic position (de Lamballerie et al, 2002). Phylogenetic trees were estimated by using the maximum-likelihood (ML) method available in TREE-PUZZLE (Strimmer & von Haesler, 1996), with 10 000 puzzling steps.…”
mentioning
confidence: 99%
“…Phylogenetically, the insect viruses form a divergent outgroup that may represent a primordial flavivirus lineage. Apart from the insect flaviviruses, the other recently discovered novel flaviviruses represent highly divergent lineages, such as Tamana bat virus (13), and Ngoye virus (20). Recently, a novel flavivirus, Nounané virus (NOUV) was isolated from a novel mosquito vector species, Uranotaenia mashonaensis in Côte d'Ivoire (23), and was shown to be phylogenetically related to the human pathogenic mosquito-borne flaviviruses.…”
mentioning
confidence: 99%